Strategi Marketing Mix pada Pengelolaan Usaha CV Rabbani Asysa dalam Tinjauan Etika Bisnis Islam - Hasriani Hasriani; Ismail Kappaja; Idayanti Idayanti (Al-Azhar Journal of Islamic Economics, 2022)
This research was conducted with the aim of knowing the marketing mix strategy in business management at CV Rabbani Asysa Makassar Branc in a review of Islamic business ethics. This research is a field research (field research) using qualitative methods, and the approaches used are economics and sociology.The results of this study indicate that the marketing mix strategy in business management at CV Rabbani Asysa Makassar Branch used is product, cost-price, promotion, communication and if viewed with Islamic business ethics it is in accordance with the indicators of unity, balance, free will, responsibility, truth, honesty and virtue. Keywords: Marketing mix strategy, Islamic business ethics